2018
DOI: 10.3390/foods7040064
|View full text |Cite
|
Sign up to set email alerts
|

Reformulation as an Integrated Approach of Four Disciplines: A Qualitative Study with Food Companies

Abstract: In 2014, the Dutch government agreed with the food sector to lower salt, sugar, saturated fat and energy in foods. To reformulate, an integrated approach of four disciplines (Nutrition & Health, Food Technology, Legislation, and Consumer Perspectives) is important for food companies (Framework for Reformulation). The objective of this study was to determine whether this framework accurately reflects reformulation processes in food companies. Seventeen Dutch food companies in the bakery, meat and convenience se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…The call for natural E-numbers and clean label foods might distract from real health issues [44,45,46]. Excessive intakes of energy, salt, saturated fat and sugar can lead to an increased risk of chronic diseases, such as cardiovascular diseases, cancer and diabetes [47,48,49,50], therefore many initiatives exist to reduce these nutrients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The call for natural E-numbers and clean label foods might distract from real health issues [44,45,46]. Excessive intakes of energy, salt, saturated fat and sugar can lead to an increased risk of chronic diseases, such as cardiovascular diseases, cancer and diabetes [47,48,49,50], therefore many initiatives exist to reduce these nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Also, removing sugar from foods requires the use of sweeteners (additives) to maintain a certain taste profile. As such, clean label may distract from what is really important in terms of health: reducing the levels of salt, sugar and saturated fat [44,45,46]. Consumers want to avoid E-numbers but are generally unaware of the consequences of removing them, such as unhealthier products, shorter shelf life and reduced quality.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely to have generated competing priorities for supermarkets, influencing their decision-making process behind product reformulation, product discontinuation and new product development. This may have included considerations for cost, convenience and product sales as well as the taste and flavour of a product [ 29 , 30 , 31 ]. As a consequence, this may have reduced their emphasis on the nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, the WHO challenged the private sector to improve the food supply and reduce levels of energy density, trans-fat, saturated fat, Na and added sugar in their products. A recent study showed that four disciplines are needed for food reformulation: Food Technology, Nutrition & Health, Legislation and Consumer Perspectives (126) . Reformulation by lowering the salt, saturated fat and sugar levels has a proven association with the reduction of the risk of chronic diseases (127) .…”
Section: Food Reformulationmentioning
confidence: 99%